2014
DOI: 10.1111/aos.12515
|View full text |Cite
|
Sign up to set email alerts
|

Toxic optic neuropathies: an updated review

Abstract: ABSTRACT.Toxic optic neuropathy (TON) is caused by the damage to the optic nerve through different toxins, including drugs, metals, organic solvents, methanol and carbon dioxide. A similar clinical picture may also be caused by nutritional deficits, including B vitamins, folic acid and proteins with sulphur-containing amino acids. This review summarizes the present knowledge on disease-causing factors, clinical presentation, diagnostics and treatment in TON. It discusses in detail known and hypothesized relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
141
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 84 publications
1
141
0
9
Order By: Relevance
“…The optic neuropathy of familial dysautonomia closely resembles that seen in mitochondrial optic neuropathies such as Leber hereditary optic neuropathy (15,19), autosomal dominant optic atrophy (20), and tobacco/alcoholic (21), Cuban epidemic (22), B 12 deficiency, and drug-related optic neuropathies (23). Pathological studies in Leber hereditary optic neuropathy and dominant optic atrophy have shown relatively preservation of melanopsin-containing ganglion cells in spite of extensive loss of the predominantly small midget/ parvocellular P-ganglion cells (17,24).…”
Section: Discussionmentioning
confidence: 92%
“…The optic neuropathy of familial dysautonomia closely resembles that seen in mitochondrial optic neuropathies such as Leber hereditary optic neuropathy (15,19), autosomal dominant optic atrophy (20), and tobacco/alcoholic (21), Cuban epidemic (22), B 12 deficiency, and drug-related optic neuropathies (23). Pathological studies in Leber hereditary optic neuropathy and dominant optic atrophy have shown relatively preservation of melanopsin-containing ganglion cells in spite of extensive loss of the predominantly small midget/ parvocellular P-ganglion cells (17,24).…”
Section: Discussionmentioning
confidence: 92%
“…The principle of the detoxification is depicted in figure 4. Currently, folic acid is recommended as an antidote in cases of methanol poisoning in human medicine 118,119 . Additionally, it was proved that formic acid is suitable for mitigating neurotoxicity pursuant to chronic ethanol intake 120 .…”
Section: Treatment Of Poisoning With the Alcoholsmentioning
confidence: 99%
“…Formate causes direct retinal damage and mitochondrial damage in the optic nerve, leading to edema and atrophy . About half of methanol‐poisoned patients develop ocular symptoms, and if the patient survives, most ocular symptoms improve or resolve …”
Section: Introductionmentioning
confidence: 99%